Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
2a2b2+2a2c2+2b2c2-a4-b4-c4
=4a2b2-(a4+2a2b2+b4)+(2b2c2+2a2c2)-c4
=2(ab)2-(a+b)2+2c2(a2+b2)+c4
=2(ab)2-[(a+b)2-2c2(a2+b2)+c4]
=2(ab)2-(b2+a2-c2)2
=[(a+b)2-c2][-(a-b)2+c2]
=(a+b-c)(a+b+c)(c-a+b)(a+c-b)
\(2a^2b^2+2a^2c^2+2b^2c^2-a^4-b^4-c^4\)
\(=4a^2b^2-\left(a^4+2a^2b^2+b^4\right)+\left(2b^2c^2+2a^2c^2\right)-c^4\)
\(=2\left(ab\right)^2-\left(a+b\right)^2+2c^2\left(a^2+b^2\right)+c^4\)
\(=2\left(ab\right)^2-\left[\left(a+b\right)^2-2c^2\left(a^2+b^2\right)+c^4\right]\\ =2\left(ab\right)^2-\left(b^2+a^2-c^2\right)^2\)
=\(\left[\left(a+b\right)^2-c^2\right]\left[-\left(a-b\right)^2+c^2\right]\\ =\left(a+b+c\right)\left(a+b+c\right)\left(c-a+b\right)\left(a+c-b\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x^2-y^2+4x+4\)
\(=\left(x+2\right)^2-y^2\)
\(=\left(x+2+y\right)\left(x+2-y\right)\)
\(4x^2-y^2+8\left(y-2\right)\)
\(=4x^2-\left(y^2-8y+16\right)\)
\(=4x^2-\left(y-4\right)^2\)
\(=\left(2x+y-4\right)\left(2x-y+4\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a ) 2a2b2 + 2b2c2 + 2a2c2 - a4 - b4 - c4
= 4a2b2 - 2a2b2 + 2b2c2 + 2a2c2 - a4 - b4 - c4
= 4a2b2 - ( a4 + 2a2b2 + b4 ) + ( 2b2c + 2a2c2 ) - c4
= 4a2b2 - [ ( a2 + b2 ) - 2.c2. ( b2 + a2 ) + c4 ]
= ( 2ab )2 - ( a2 + b2 - c2 )
= ( 2ab - a2 - b2 + c2 )( 2ab + a2 + b2 - c2 )
= [ c2 - ( a2 - 2ab + b2 ) ] . [ (a2 + 2ab + b2 ) - c2 ]
= [ c2 - ( a - b )2 ] . [ ( a + b )2 - c2 ]
= ( c - a + b )( c + a - b )( a + b - c )( a + b + c )
b ) x2 - 10x + 24
= ( x2 - 10x + 25 ) - 1
= ( x - 5 )2 - 12
= ( x - 5 - 1 )( x - 5 + 1 )
= ( x - 6 )( x - 4 )
![](https://rs.olm.vn/images/avt/0.png?1311)
1. x^3-19x-30
=x^3-25x+6x-30
=x(x^2-25)+6(x-5)
=x(x+5)(x-5)+6(x-5)
=(x-5)(x^2+5x+6)
=(x-5)(x^2+2x+3x+6)
=(x-5)[x(x+2)+3(x+2)]
=(x-5)(x+2)(x+3)
2.
a + b + c = 0
<=> (a + b + c)² = 0
<=> a² + b² + c² + 2(ab + bc + ca) = 0
<=> a² + b² + c² = -2(ab + bc + ca) ------------(1)
CẦn chứng minh:
2(a^4 + b^4 + c^4) = (a² + b² + c²)²
<=> 2(a^4 + b^4 + c^4) = a^4 + b^4 + c^4 + 2(a²b² + b²c² + c²a²)
<=> a^4 + b^4 + c^4 = 2(a²b² + b²c² + c²a²)
<=> (a² + b² + c²)² = 4(a²b² + b²c² + c²a²) ---(cộng 2 vế cho 2(a²b² + b²c² + c²a²) )
<=> [-2(ab + bc + ca)]² = 4(a²b² + b²c² + c²a²) ----(do (1))
<=> 4.(a²b² + b²c² + c²a²) + 8.(ab²c + bc²a + a²bc) = 4(a²b² + b²c² + c²a²)
<=> 8.(ab²c + bc²a + a²bc) = 0
<=> 8abc.(a + b + c) = 0
<=> 0 = 0 (đúng), Vì a + b + c = 0
=> Đpcm
Ta có:
\(A=a^4+b^4+c^4-2a^2b^2-2a^2c^2-2b^2c^2\)
\(=a^4+b^4+c^4+2a^2b^2-2a^2c^2-2b^2c^2\) \(-4a^2b^2\)
\(=\left(a^2+b^2-c^2\right)^2-4a^2b^2\) \(=\left(a^2+b^2-c^2\right)^2-\left(2ab\right)^2\)
\(=\left(a^2+b^2-c^2-2ab\right)\left(a^2+b^2-c^2+2ab\right)\)
\(=\left[\left(a-b\right)^2-c^2\right]\left[\left(a+b\right)^2-c^2\right]\)
\(=\left(a-b-c\right)\left(a-b+c\right)\left(a+b-c\right)\left(a+b+c\right)\)